Literature Based Model as an Effort to Build Pedagogic Literacy Ability of Students Elementary School - Zakaria Zakaria; Imam Mahfud (International Journal on Advanced Science, Education, and Religion, 2021)
The literacy learning paradigm must be able to direct students to understand the values ​​of pedagogic literacy. The government policy in the Regulation of the Minister of Education and Culture Number 23 of 2015 proclaims the school literacy movement or Gerakan Literasi Sekolah requiring students to read for 15 minutes as an effort to build a passion for reading, fostering imagination through reading activities with educational messages. Pedagogic literacy values ​​must be built from an early age in an effort to create students with character. One learning model that is considered capable of building students' pedagogic literacy skills is the literature based model. The artile aims to analyze the description of pedagogic literacy in elementary school learning and the didactic design of a literature-based model in building the pedagogic literacy skills of elementary school students. The researchers used the content analysis or meta-analysis method. Sources of data in this study are journals and books related to literature-based models and pedagogic literacy. Then, the object of this research is the didactic design of the literature based model in building the pedagogic literacy skills of elementary school students. The result show that the literature-based model shows an increase in activity students including students' enthusiasm in following lessons, student interaction with teachers, student interaction with students, and student participation in concluding learning. Keywords: Pedagogic Literacy Ability, Model Pedagogic Literacy, Students Literation